Productivity, competitiveness and the internal market: A critical analysis of the Letta and Draghi reports - Górriz López, Carlos (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
Enrico Letta and Mario Draghi produced two reports on the future of the European Union.They stress a worrying decline in productivity and competitiveness compared to the United States andChina, as well as inefficiencies within the Internal Market. They analyse the causes of this situation andpropose measures that essentially consist of deepening in the Single Market integration, creating Europeanchampions, closing the technological gap, combining the green transition with increased competitiveness,and reducing dependencies on third parties. The viability of these measures raises doubts. Politically,achieving a consensus will be extremely difficult. Legally, it faces the problem of the principle ofcompetence allocation. Economically, securing the necessary financing poses risks to fiscalsustainability.
Keywords: Single Market; open strategic autonomy; green transition and digital transition